Empowering Musical Engagement: Applying Self Determination Theory in Digital Music Education for Generation Z - Nuristama, Ramadhina Ulfa (Harmonia : Journal of Music and Arts, 2024)
This study explores the application of Self Determination Theory (SDT) in digital music education for Generation Z learners in Indonesia. Drawing on autonomy, competence, and relatedness, the study investigates how motivational constructs can be embedded in digital platforms to enhance student engagement and creativity. Using a mixed methods approach, 94 secondary students participated in an 8 week digital music project using DAWs such as BandLab and Soundtrap. Data were collected through pre/post motivation surveys, project reflections, and peer feedback logs. Results revealed significant increases in perceived autonomy (3.2→4.1), competence (3.0→4.3), and relatedness (2.8→4.0), supported by thematic analysis of digital interactions. Collaborative feedback, genre based task choice, and scaffolded skill development were found to be critical motivational drivers. The integration of Universal Design for Learning (UDL) principles further supported inclusive and engaging curriculum design. The study concludes that SDT aligned digital practices foster intrinsic motivation and sustained participation in music education. Implications are drawn for curriculum design, teacher training, and national education policy, particularly in contexts facing infrastructural disparities.